Effects of Dark Septate Endophytes on the Performance and Soil Microbia of Lycium ruthenicum Under Drought Stress - He, Chao; Han, Tingting; Tan, Ling; Li, Xianen (Frontiers in Plant Science, 2022)
This study mainly aimed to investigate the effects of dark septate endophytes (DSE) (Neocamarosporium phragmitis, Alternaria chlamydospore and Microascus alveolaris) on the performance and microbial community composition in the rhizosphere soil of Lycium ruthenicum Murr under drought stress. Differences in plant performance, such as plant growth and physiological parameters, and soil parameters and microbial community composition under all the treatments were examined. Three DSE strains could colonize the roots of L.ruthenicum successfully, and they established a positive symbiosis with the host plants depending on DSE species and water availability. The greatest benefits of DSE inoculation occurred in drought stress conditions. Specifically, N. phragmitis and A. chlamydospore exhibited positive effects on plant biomass, growth, and physiological parameters in L.ruthenicum plants under drought stress conditions. In additions, DSE inoculation significantly increased AM fungi, gram-negative bacteria and actinomycetes content under drought stress. Variance decomposition analysis showed that DSE was the most important factor affecting the growth and physiological parameters of host plants, and the interaction between DSE and water conditions was the most important interaction factor restricting soil microbial content. Mantel test and structural equation model (SEM) analysis demonstrated that the positive effects of DSE on host plants varied with strain and plant parameters under different water conditions. These data contribute to the understanding of the ecological function of DSE for the cultivation of L.ruthenicum plants in drylands.